Supplementation with Glucosamine Has no Adverse Effects on Glycemic Level and Insulin Resistance in Type 2 Diabetic Patients - Zohreh Mazloom; Mohammad Hossein Dabbaghmanesh; Mahsa Moazen; Sara Bagheri (Shiraz University of Medical Sciences, 2015)
Background: Use of glucosamine as an alternative treatment for osteoarthritis is becoming more frequent, including in those who have diabetes at the same time. The results from in vitro and animal studies propose that glucosamine may inversely affect glucose metabolism. However, the recommended dose of oral glucosamine in healthy people or diabetics did not have such effects consistently. The aim of the present study was to assess the effect of glucosamine on glycemic control and insulin resistance in type 2 diabetic patients. Methods: Fifty-four patients with type 2 diabetes participated in this randomized, double-blind, placebo-controlled study. The participants were assigned to receive 1500 mg glucosamine hydrochloride or placebo for 12 weeks. After determining their baseline characteristics, body mass index and dietary intake components, fasting blood glucose and fasting insulin were measured at weeks of 0, 8, and 12. Indices of insulin function including quantitative insulin sensitivity check index (QUICKI) and homeostasis model assessment of insulin resistance (HOMA-IR) were calculated by specific formulas. Independent t-test and general linear model repeated measures were used to analyze the data. Results: In the glucosamine group, the means of fasting blood glucose and insulin were 107.31±24.07 mg/dl and 8.75±4.37 μu/ ml, respectively at baseline, which reached 112.38±31.50 and 9.10±4.17 at week 12. In the placebo group, the mean for fasting blood glucose and insulin were 103.84±24.15 and 9.79±4.02 at the beginning of the study, which reached to 111.40±26.43 and 8.58±3.68 at week 12. The results showed that there were no significant differences in fasting blood glucose, insulin, HOMA-IR and QUICKI indices at all the studied time points (weeks of 0, 8 and 12) within or between the groups. Conclusion: Twelve weeks of a normal recommended dose of glucosamine supplements may not have adverse effects on glycemic control and insulin resistance in type 2 diabetic patients. Trial registration number: IRCT2014031811785N2.